Loss of Nexilin function leads to a recessive lethal fetal cardiomyopathy characterized by cardiomegaly and endocardial fibroelastosis. Issue 6 (15th February 2022) - Johansson, Josefin; Frykholm, Carina; Ericson, Katharina; Kazamia, Kalliopi; Lindberg, Amanda; Mulaiese, Nancy; Falck, Geir; Gustafsson, Per‐Erik; Lidéus, Sarah; Gudmundsson, Sanna; Ameur, Adam; Bondeson, Marie‐Louise; et al.
Abstract: The Nexilin F‐Actin Binding Protein (Nexilin) encoded by NEXN is a cardiac Z‐disc protein important for cardiac function and development in humans, zebrafish, and mice. Heterozygote variants in the human NEXN gene have been reported to cause dilated and hypertrophic cardiomyopathy. Homozygous variants in NEXN cause a lethal form of human fetal cardiomyopathy, only described in two patients before. In a Swedish, four‐generation, non‐consanguineous family comprising 42 individuals, one female had three consecutive pregnancies with intrauterine fetal deaths caused by a lethal form of dilated cardiomyopathy. Whole‐exome sequencing and variant analysis revealed that the affected fetuses were homozygous for a NEXN variant (NM_144573:c.1302del;p.(Ile435Serfs*3)). Moreover, autopsy and histology staining declared that they presented with cardiomegaly and endocardial fibroelastosis. Immunohistochemistry staining for Nexilin in the affected fetuses revealed reduced antibody staining and loss of striation in the heart, supporting loss of Nexilin function. Clinical examination of seven heterozygote carriers confirmed dilated cardiomyopathy (two individuals), other cardiac findings (three individuals), or no cardiac deviations (two individuals), indicating incomplete penetrance or age‐dependent expression of dilated cardiomyopathy. RNA sequencing spanning the variant in cDNA blood of heterozygote individuals revealed nonsense‐mediated mRNA decay of the mutated transcripts. In the current study, we present the first natural course of the recessively inherited lethal form of human fetal cardiomyopathy caused by loss of Nexilin function. The affected family had uneventful pregnancies until week 23–24, followed by fetal death at week 24–30, characterized by cardiomegaly and endocardial fibroelastosis.